The Implementation of Polluter-Pays Principles on Marine Pollution Caused by Vessels in Indonesia (The Study of Oil Spill Cases) - Zhafirah Ulfah; Nellyana Roesa (Syiah Kuala Law Journal, 2020)
Nowadays, there are some marine pollution cases caused by oil spill from vessels. These cases give a significant impact on marine environment and threatening human’s life. Therefore, law enforcement is needed.One of the principles that can be used in solving this problem is Polluter-Pays principles. This principle found in the 16th principle of the Rio Declaration on Environment and Development on 2002. The requirement of the principle is cost of pollution should be borne by the person responsible for causing the pollution. National authorities should endeavor to promote the internalization of environmental costs and the use of economic instruments. This article aims to find out the implementation of polluter pays principles in Indonesia, especially in study of oil spill. Polluter pays principle can be used as one of solution in helping country overcome the loses oil spill cases within Indonesian waters. One of the challenges is Indonesia need a specific instrument used as a mechanism for calculating the loss or damage that should be paid by the polluters.